(Invited) Internal Photoemission of Electrons from 2-Dimensional Semiconductors. (16th August 2017) - Afanas'ev, Valery V.; Chiappe, Daniele; Leonhardt, Alessandra; Houssa, Michel; Huyghebaert, Cedric; Radu, Iuliana; Stesmans, Andre
Abstract : Experimental analysis of photocurrent spectra in Si/SiO2 /transition metal dichalcogenide (TMD) structures indicates the dominant contribution of internal photoemission (IPE) of electrons from the TMD valence band. Spectral distributions of this signal can be used to determine energy position of the band edges in the TMD film with respect to the common reference level of the oxide conduction band as demonstrated for the cases of sulfurization-grown MoS2, WS2, and their heteostructures. Furthermore, IPE allows one to trace the impact of sample processing on the electrostatic potential distribution at the TMD/oxide interface.